Alisher Navoi is a traditional hero of the epic "Layli and Majnun". Artistry in the image (Texas Journal of Philology, Culture and History, 2023)
In this article, we can see the process (genesis) of the formation of the high artistic and traditional image of the heroes of the epic "Layli and Majnun" by His Holiness Navoi: the lovers Layli and Majnun on the example of the legendary love story.